Reconsidering No man knows my history: Fawn M. Brodie and Joseph Smith in retrospect - Bringhurst, Newell G., editor; Utah State University Press, publisher (Colorado State University. Libraries, 1996)
Fawn Brodie's biography of the founding Mormon prophet has received both praise and condemnation since its publication in 1945. In 1995, at a symposium to mark its fiftieth anniversary, several scholars gathered together to re-examine Brodie, her Joseph Smith biography and its continuing importance. Bringhurst has brought together many of the essays from that meeting.
A biography of the biography: the research and writing of No man knows my history / Newell G. Bringhurst -- Applause, attack, and ambivalence: varied responses to No man knows my history / Newell G. Bringhurst -- Secular or sectarian history?: a critique of No man knows my history / Marvin S. Hill -- Fawn McKay Brodie: at the intersection of secularism and personal alienation / Mario S. De Pillis -- Literary style in No man knows my history: an analysis / Lavina Fielding Anderson -- Fawn Brodie on Joseph Smith's plural wives and polygamy: a critical view / Todd Compton -- From old to new Mormon history: Fawn Brodie and the legacy of scholarly analysis of Mormonism / Roger D. Launius.
Keywords: Mormon Church -- Presidents -- Biography; Mormons -- United States -- Biography; Brodie, Fawn McKay, 1915-1981. No man knows my history; Smith, Joseph, Jr., 1805-1844